2017
DOI: 10.1128/jvi.01103-17
|View full text |Cite
|
Sign up to set email alerts
|

B Cell-Specific Expression of Ataxia-Telangiectasia Mutated Protein Kinase Promotes Chronic Gammaherpesvirus Infection

Abstract: Manipulation of host cellular pathways is a strategy employed by gammaherpesviruses, including mouse gammaherpesvirus 68 (MHV68), in order to negotiate a chronic infection. Ataxia-telangiectasia mutated (ATM) plays a unique yet incompletely understood role in gammaherpesvirus infection, as it has both proviral and antiviral effects. Chronic gammaherpesvirus infection is poorly controlled in a host with global ATM insufficiency, whether the host is a mouse or a human. In contrast, ATM facilitates replication, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Enzyme-linked immunosorbent assay (ELISA). Total, MHV68-specific, LCMV-specific, and dsDNA immunoglobulin levels were determined as previously described (14,21,(47)(48)(49)(50). Briefly, Nunc MaxiSorp plates (Fisher Scientific, Pittsburgh, PA) were coated with either anti-mouse IgG antibodies (heavy plus light chain) or anti-mouse IgM antibodies (total IgG and IgM levels) (Jackson ImmunoResearch, West Grove, PA), UV-irradiated MHV68 virus stock-PBS (Stratalinker UV Crosslinker 1800; Agilent Technologies, Santa Clara, CA) (740,000 J/cm 2 ϫ 2), LCMV clone 13-infected BHK cell lysates, or dsDNA from Escherichia coli (12.5 g/ml; Sigma-Aldrich, St. Louis, MO) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay (ELISA). Total, MHV68-specific, LCMV-specific, and dsDNA immunoglobulin levels were determined as previously described (14,21,(47)(48)(49)(50). Briefly, Nunc MaxiSorp plates (Fisher Scientific, Pittsburgh, PA) were coated with either anti-mouse IgG antibodies (heavy plus light chain) or anti-mouse IgM antibodies (total IgG and IgM levels) (Jackson ImmunoResearch, West Grove, PA), UV-irradiated MHV68 virus stock-PBS (Stratalinker UV Crosslinker 1800; Agilent Technologies, Santa Clara, CA) (740,000 J/cm 2 ϫ 2), LCMV clone 13-infected BHK cell lysates, or dsDNA from Escherichia coli (12.5 g/ml; Sigma-Aldrich, St. Louis, MO) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…It is reasonable to suggest that MHV68 likewise triggers p53 through an ATM-mediated DDR, and we previously demonstrated that this is the case during lytic viral replication(39). Whether MHV68 causes ATM activation during latency establishment specifically in infected B cells has not been directly evaluated.However, the observation that B-cell-specific deletion of ATM correlates with a global defect in MHV68 latency(19), rather than the early enhancement in infection we observed in the absence of p53 during initial colonization of the host, suggests that ATM and p53 function independently in latently infected cells in vivo. Alternatively, it is possible that p53 induction occurs during MHV68 infection as a consequence of replication stress due to virus-driven cellular proliferation.…”
mentioning
confidence: 69%
“…A role for ATM in restricting MHV68 infection in vivo recently was tested; however, ATM deficiency did not promote enhanced latent infection by MHV68 (17). Rather, ATM facilitates B cell latency (18,19).…”
mentioning
confidence: 99%
“…Intranasal inoculation of 6–8 week old mice with 10 4 PFU of wild type murine gammaherpesvirus 68 (MHV68; WUMS strain) or 15 μl of phosphate buffered saline(PBS) was performed under light anesthesia, as previously reported [22]. MHV68-innoculated mice were housed separately from carrier-inoculated mice for the duration of the study.…”
Section: Methodsmentioning
confidence: 99%